2003
DOI: 10.1111/j.1349-7006.2003.tb01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of allelic loss on chromosome 6q within heterogeneous prostate carcinoma

Abstract: A number of genetic events have been reported in prostate carcinogenesis, including frequent loss of heterozygosity (LOH) on chromosomes 8q, 10q, 16q and 18q. In samples of heterogeneous, multifocal prostate carcinomas, we focused on chromosome 6q using PCR-based techniques with 15 microsatellite markers to identify the specific 6q deletion within tumors. LOH of one or more polymorphic markers was detected in 10 of 21 tumors (48%). Two of these 10 tumors demonstrated LOH in all cancerous foci at specific loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
(44 reference statements)
2
17
1
Order By: Relevance
“…Primary tumors show a rather heterogeneous expression of proliferationassociated markers, such as Ki-67, and apoptosis-induced DNA fragmentation, showing the asynchronous growth of a prostate tumor (8). Microsatellite-based studies on microdissected tissue resulted in the identification of areas in the primary tumor with different alterations associated with a distinct histologic differentiation (3,4,9).…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumors show a rather heterogeneous expression of proliferationassociated markers, such as Ki-67, and apoptosis-induced DNA fragmentation, showing the asynchronous growth of a prostate tumor (8). Microsatellite-based studies on microdissected tissue resulted in the identification of areas in the primary tumor with different alterations associated with a distinct histologic differentiation (3,4,9).…”
Section: Discussionmentioning
confidence: 99%
“…CGH and cytogenetic studies have shown that frequent genetic alterations occur in the 6q15-22 region and indicate that 1 or more TSGs are located there. [26][27][28][29][30] Three potential candidate genes are present in this region, and they encode cell-cycle regulatory protein cyclin C, thiol-specific antioxidant protein 1 and the glutamate receptor iontropic kainate 2.…”
Section: Chromosomal Lossesmentioning
confidence: 99%
“…We employed PCR-SSCP analysis to pre-screen for mutations in exons 5-8 of the p53 gene; sequencing primers used have been previously described [20]. Samples showing mobility shifts in SSCP analysis were further analyzed by DNA sequencing.…”
Section: P53 Mutation Analysismentioning
confidence: 99%
“…Only samples heterozygous for a given locus were regarded to be informative; loci homozygosity and/or microsatellite instability rendered any particular sample noninformative. Samples were considered to show LOH when a peak allele signal from tumor DNA was reduced by 50% compared with the normal tissue counterpart [20].…”
Section: Loh Assaymentioning
confidence: 99%